Nowcasting severe convection in the Alpine region: the COALITION approach. (28th October 2013) - Nisi, L.; Ambrosetti, P.; Clementi, L.
<x xml:space="preserve">Abstract</x> The purpose of the operationally oriented system named the Context and Scale Oriented Thunderstorm Satellite Predictors Development (COALITION) is automatically to detect severe thunderstorms early in their development and consequently help weather forecasters to increase lead times when issuing severe weather warnings. This new object‐oriented system integrates data provided by different sources. Data from the Meteosat Second Generation Rapid Scan Service, weather radar and numerical weather prediction, as well as climatology, are utilized by the system. One of its primary purposes is to use all the best operationally available information about convective processes and to integrate it into a heuristic model. Furthermore the orographic forcing, which is often neglected in heuristic nowcasting models, is taken into account and included in the system as an additional convective triggering mechanism. This is particularly important for areas characterized by complex orography like the Alpine region. The COALITION algorithm merges evolving thunderstorm properties with selected predictors. The forecast evolution of the storm is the result of the interaction between convective signatures and surrounding storm environment. Eight different 'object‐environment' interactions are analyzed in eight modules, providing ensemble nowcasts of thunderstorm attributes (satellite‐ and radar‐based) for the following 60 min. All ensemble nowcasts are then combined through a weighting and thresholding scheme and the results are summarized into a single graphical map in order to facilitate user interpretation. The COALITION nowcast system has an update frequency of 5 min. The output highlights the cells having a high probability of severe thunderstorm development within the next 30 min. Verification statistics confirm that COALITION is able to nowcast the intensity of developing convective cells with sufficient skill up to a lead time of about 20 min.